Evaluation of the relationship between digital mammography radiation dose and patient age, breast volume and density - ECE, Bünyamin (Journal of Health Sciences and Medicine, 2023)
Aims: To determine the average radiation dose values in patients who underwent routine screening mammography in our hospital, establish the relationship between breast density and volume, and investigate other factors affecting radiation dose. Methods: Screening bilateral mammography was retrospectively evaluated within the specified period of 2 months. Patient age, breast density ratio, mammographic size of the breast, calculated breast volume, tube voltage, current, exposure time (ms), compression force (kg), compression thickness (mm), and radiation dose (mGy) given in each projection were recorded separately for each patient. According to the BI-RADS, breast densities classified as types A-B were considered non-dense, while types C-D were considered dense breasts. The 75th percentile dose value (mGy) was chosen as the cutoff for high dose group. Logistic regression analyses were used to examine the factors affecting radiation dose. Results: 1720 mammograms from 430 patients were studied. 276 (64.2%) breasts were non-dense, while 154 (35.8%) breasts were dense. The mean total breast volume was 595±334 ml, compression thickness was 36.5±12.0 mm, and radiation dose was 2.04±0.75 mGy. There was a negative correlation between radiation dose and age (r=-0.330, p
Keywords: Mammography; breast; radiation dosage; diagnostic imaging; breast density; diagnostic screening programs; Radyoloji ve Organ Görüntüleme; Radiology and Organ Imaging; 3. Good health